The black Hundreds movement study in Russian historical science in the 1990-2000s - Kuritsyn Artem Igorevich (Studia Humanitatis, 2025)
The paper examines the Russian historiography of the Black Hundred movement at the turn of the 20th and 21st centuries. Particular importance is given to key studies that determined its development during the period under review. The author emphasises close attention of Russian researchers to a number of problems including regional characteristics of extreme right-wing parties and organizations, their numbers and composition, and internal contradictions.